Effect of Distillery Spent Wash (DSW) and Fertilizer on Growth and Chlorophyll Content of Sugarcane (Saccharum officinarum l.) Plant - G.Pradhan1, M.K.Misra2, P.Rath1 (Recent Research in Science and Technology, 2011)
A field experiment was conducted with distillery spent wash (DSW) collected from Aska Co-operative Sugar Industries Ltd., Aska, Odisha, India and other two types of treatments viz; inorganic fertilizer and cow dung to observe a comparative effect on growth and chlorophyll content using sugarcane variety Co1274 as the test crop. The experiment was formulated with four treatments (50% DSW, 100% DSW, fertilizer & fertilizer + cow dung) each with three replicates and one set of control. The growth parameters such as height of the plant, length and girth of stem, breadth of leaves, number of leaves and number of tillers per plant, leaf area index and total chlorophyll content of sugarcane plant were estimated during different growth periods in all treatments. All the parameters showed an increasing trend from the control except 100% distillery spent wash, where a declining trend over the control in all parameters was observed. Maximum growth and chlorophyll content was observed in 50% distillery spent wash as compared with two different types of fertilizers.